2021
DOI: 10.1111/acfi.12814
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement systems and client performance in fee‐generating not‐for‐profit human service organisations

Abstract: We use survey and archival data from 271 fee-generating not-for-profit human service organisations in Australia to examine how the use of performance measurement systems affects those organisations' client performance. Using Simons' levers of control, we find that interactive and diagnostic uses of performance measurement systems are positively related to client performance. We also find beliefs control to positively moderate the relation between diagnostic use of performance measurement systems and client per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 78 publications
2
9
0
Order By: Relevance
“…Our findings demonstrating that the extent of interactive PMS use is indirectly associated with organizational performance through empowerment and creativity expand upon Appuhami (2019) and Hall (2008) empirical findings. Finally, these findings expand upon the work of Harrison et al (2022) , which is based on survey data from senior managers in organizations. Compared with earlier theoretical and empirical work (e.g., Hall, 2008 ; Harrison et al, 2022 ), we simultaneously broadened the nature of the sample, indicating that interactive use of PMSs is beneficial for psychological empowerment at all levels of managers.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Our findings demonstrating that the extent of interactive PMS use is indirectly associated with organizational performance through empowerment and creativity expand upon Appuhami (2019) and Hall (2008) empirical findings. Finally, these findings expand upon the work of Harrison et al (2022) , which is based on survey data from senior managers in organizations. Compared with earlier theoretical and empirical work (e.g., Hall, 2008 ; Harrison et al, 2022 ), we simultaneously broadened the nature of the sample, indicating that interactive use of PMSs is beneficial for psychological empowerment at all levels of managers.…”
Section: Discussionsupporting
confidence: 57%
“…Finally, these findings expand upon the work of Harrison et al (2022) , which is based on survey data from senior managers in organizations. Compared with earlier theoretical and empirical work (e.g., Hall, 2008 ; Harrison et al, 2022 ), we simultaneously broadened the nature of the sample, indicating that interactive use of PMSs is beneficial for psychological empowerment at all levels of managers. Consequently, the study highlights the importance of interactive PMS use in achieving higher levels of individual behavior.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The purpose of this study is to examine the effect of performance measurement systems (PMS) and organisational culture on revenue growth in not‐for‐profit organisations (NFPs) in the aged care sector in Australia. While several prior studies have examined the effect of PMS and the use of accountability mechanisms on NFPs’ social performance (e.g., Harrison et al ., 2021; Jiao, 2021), none has examined the effect on financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the NFP and public sectors, recent studies by Felicio et al (2021) and Harrison et al (2021) hypothesized and found positive associations between the use of MCS and performance outcomes proxied by the accomplishment of effectiveness, efficiency, and service quality objectives (Felicio et al, 2021), and NFP client performance indicated by, inter alia, client satisfaction, and client base growth (Harrison et al, 2021). However, while there is substantial research that has examined the consequences of MCS, there is little that speaks to the antecedents.…”
mentioning
confidence: 99%